HISTOPATHOLOGICAL AND BIOLOGICAL BEHAVIOR OF BREAST CANCER IN ELDERLY KURDISH WOMEN - Saeed, Kamal Ahmad; Salih, Shewaz Abdulla Faqe (Journal of Sulaimani Medical College, 2025)
Background Breast cancer is the most prevalent cancer in women, with incidence and mortality increasing markedly with age. Objective This study aimed to determine the clinicopathological features and biological behaviors of breast cancer patients in elderly Kurdish women. Materials and Methods We retrospectively evaluated the clinicopathological and biological features of breast cancer in elderly Kurdish women (≥65 years; n = 143) between 2015 and 2021. This cross-sectional study was carried out at the Hiwa haematology-oncology hospital in the Iraqi Kurdistan province of Sulaymaniyah. According to age, patients were divided into groups 1 (65–74 years, N=112) and 2 (75 years or older, N=31). Clinicopathological characteristics including tumor histology, histological grade, estrogen (ER) and progesterone (PR) and human epidermal growth factor 2 (HER2) status, molecular subtypes, tumor sizes (T), lymph node status (N), lymphovascular invasion (LVI), distant metastasis (M), clinical stage, and tumor focality with laterality were all assessed. Results The mean age of the study population was 71.4. The most common histopathological type of breast cancer was invasive ductal carcinoma, followed by invasive lobular carcinoma and papillary carcinoma. Hormone receptor positivity rates were high, and the HER2 status was mostly negative. Luminal A and B (79.7%) were the most frequent types; triple negative (15.2%) was high. The mean age was 72.3 for group 1 (range 65-74) and 84.9 for group 2 (range 75 and older). Excluding symptomatic presentation, progesterone receptor status, and metastasis category, no statistically signifi cant difference was found between the two groups. At the time of presentation, every patient in group 2 had symptoms (p=0.047). Conclusion Our study results showed that breast cancer in the elderly (≥65 years) patients in Kurdish seemed to have more aggressive clinical, pathological, and biological characteristics than older women worldwide.
Keywords: Clinicopathological; Breast cancer; Elderly Kurdish women